Information Literacy Threshold Concepts and the Association of College and Research Libraries' Framework for Information Literacy for Higher Education - Schaub, Gayle; McClure, Hazel (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2017)
The 2014 release of the Association of College and Research Libraries’ Framework for Information Literacy for Higher Education had a significant impact on information literacy scholarship and practice in the United States. The revision process of the previous Competency Standards and the purpose and implementation of the new Framework are still widely discussed as librarians work out what the Framework means to individual institutions and to information literacy as a whole. Organized around six threshold concepts in information literacy as identified in recent research, the Framework reflects developments in the information landscape as threshold concepts have become influential. The authors, who began their research in threshold concepts at the same time as the use and discussion of information literacy threshold concepts increased in the United States, discuss how their work fits into a larger, national conversation on conceptual information literacy instruction and the creation of a high-profile document. Die Verabschiedung des Framework for Information Literacy for Higher Education der Association of College and Research Libraries 2014 hatte beachtliche Auswirkungen auf Theorie und Praxis der Vermittlung von Informationskompetenz in den USA. Der Überarbeitungsprozess der früheren Standards Informationskompetenz sowie Zielrichtung und Umsetzung des neuen Framework werden nach wie vor breit diskutiert, da Bibliothekar/inn/e/n nun konkretisieren, was das Framework für ihre jeweilige Einrichtung und für Informationskompetenz insgesamt bedeutet. Indem es um sechs threshold concepts gruppiert ist, die die aktuelle Forschung zu Informationskompetenz identifiziert hat, bezieht das Framework gezielt Entwicklungen der Informationslandschaft auf diese richtungsweisenden threshold concepts. Die Autorinnen, die ihre Untersuchungen zu threshold concepts just zu der Zeit begannen, zu der der Einsatz von und die Diskussion um threshold concepts in den USA sich ausweitete, legen dar, wie sich ihre Arbeit in einen landesweiten Diskurs um konzeptionell orientierte Vermittlung von Informationskompetenz und die Erstellung eines von der Öffentlichkeit vielbeachteten Grundlagenpapiers einfügt.